Dynamics of Cavitation/Air Bubbles in Seawater-Based Viscoelastic Fluids - Siginer, D (Elsevier Ltd, 2026)
During the navigation of underwater vehicles, due to chemical reactions and cavitation phenomena, small-scale bubbles are inevitably generated around the vehicle. These small-scale bubbles pose significant challenges in the stealth performance of the underwater vehicle navigation, caused by the distinct characteristics of prolonged persistence and wide spatial distribution of the small-scale bubbles. Viscoelastic turbulence drag reduction is one of the means of reducing drag for underwater vehicles. During the use of this drag reduction agent, the movement of bubbles around the vehicle in the viscoelastic fluid is inevitable. Therefore, the dynamics of the cavitation and air bubbles in sea-based viscoelastic fluids were experimentally investigated in present work. The results demonstrate that increasing seawater salinity and viscoelastic fluid concentration reduces cavitation bubble size, under identical conditions. The bubble lifetime increases with bubble size, although it is markedly shorter in seawater compared to other media. Both millimeter- and submillimeter-sized bubbles grow larger with higher viscoelastic fluid concentrations. We determine that elevated viscoelastic fluid concentrations dampen oscillation amplitudes during bubble ascent. Changes in seawater salinity have no significant effect on the dynamic characteristics of cavitation bubbles and bubbles in general. © 2025 Elsevier Ltd.